1997
DOI: 10.1038/sj.bmt.1700671
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of CD34+ cell dose to early and late hematopoiesis following autologous peripheral blood stem cell transplantation

Abstract: Summary:unstimulated peripheral blood contains less than one tenth the number of progenitors as marrow, the total number present in mobilized leukapheresis harvests and infused We evaluated early and late hematopoietic reconstitution in 27 patients with advanced lymphoma, Hodgto reconstitute hematopoiesis may exceed marrow by several fold. 2,3 kin's disease, and breast or ovarian cancer after treatment using high-dose/myeloablative conditioning Clinical studies have shown that 'mobilized' PBSC transplants are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
110
2
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 3 publications
(1 reference statement)
8
110
2
2
Order By: Relevance
“…[7][8][9]12,13,16 The optimal number of CD34 + cells for rapid and consistent engraftment in PBSCT is 5.0 ϫ 10 6 /kg. 12 In the present study, the correlation between the number of CD34 + cells and platelet recovery was not significant (r = Ϫ0.27), in contrast to previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9]12,13,16 The optimal number of CD34 + cells for rapid and consistent engraftment in PBSCT is 5.0 ϫ 10 6 /kg. 12 In the present study, the correlation between the number of CD34 + cells and platelet recovery was not significant (r = Ϫ0.27), in contrast to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] As for platelet recovery, few studies have been reported; some have shown that the number of CFU-GM and CD34 + cells correlate with platelet recovery, 7-14 but others have not shown a significant correlation. 15,16 Recently, specific markers for megakaryocyte progenitors such as colony-forming unit megakaryocyte (CFU-MK) and CD34 + /CD41 + or CD34 + /CD61 + cells have predicted platelet engraftment in PBSCT.…”
mentioning
confidence: 99%
“…Apheresis failures can be reduced if reliable indicators are available for measuring adequate mobilization of CD34 + cells. The WBC count during the recovery phase following the chemotherapy-induced nadir is widely used as the practical indicator of time to initiate apheresis, but the counts do not correlate well with the number of mobilized CD34 + cells [18][19][20]30,31]. Several previous studies reported that the rate of WBC recovery could be used to predict the most effective time for apheresis [5,9,27,32,33], but in our experience, the correlation between WBC recovery rate and the CD34 + cell number was moderate, indicating that this parameter is not useful in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The best time to begin PBSC collection after the chemotherapyinduced nadir without cytokine support is reported as the day of returning the WBC count to >1,000/mL [14,15], while the WBC count >3,000 or >10,000/mL is recommended when cytokine support is combined [3,16]. The correlation between the WBC count and the number of CD34 + cells in apheresis products, however, is not high, or even non-existent [8,[17][18][19][20]. Therefore, there exists a need for a good indicator that can be obtained from ordinary clinical data that will reduce the frequencies of failed apheresis.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 For this reason some centers, including our own, have opted to limit the transplant infusion to that number or less for some patients. Thus for many transplant recipients, excess cells have been cryopreserved and are subsequently available for infusion.…”
Section: Introductionmentioning
confidence: 99%